Data Analysis and Nudging for Green Transportation - Jemea, Lady Limunga (UiT Norges arktiske universitet, 2019)
The topic of a more sustainable environment has been a core factor to governments and the public for many years. Sustainability in land transportation brings about less emission of greenhouse gases, less pollution, less traffic, a healthier and more active society. Ignorance to sustainability has brought about several environmental and human concerns including global warming. Global warming is the measured increase in the temperature of the earth. Multiple factors have been known to contribute to global warming which fall under anthropological and natural causes. In this thesis, we focus on one of the several human activities which contributes to global warming, road transportation. Several means of road transportation exist with some being more sustainable than others. The goal for this thesis is to introduce a system of information and digital nudging where users of the system are presented with vital information and nudge messages which could influence their transportation choices towards more sustainable options. I approached this proposed solution by doing analysis of data from multiple sources and channeling the results of the analysis in a web application through push notifications. While the data and implementation for this thesis is specific for the municipality of Tromsø, Norway, the concept can easily be extended and adapted to suit any other town or country.